Strategi Manajemen Kurikulum Dalam Mengoptimalkan Podcast Sebagai Media Pembelajaran Inovatif - Irwan Maulana; Pramudyasari Nur Bintari; Arum Puri Suryandari; Ali Rahman; Novi Nurhayati (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to analyze curriculum management strategies for optimizing podcasts as an innovative and relevant learning medium for 21st-century education. The use of podcasts is growing along with the increasing integration of technology into the learning process, necessitating an appropriate curriculum management approach for effective implementation. This study employed a qualitative literature review, reviewing various scientific sources related to curriculum planning, resource organization, podcast-based learning implementation, and curriculum evaluation. The results indicate that strengthening systematic planning, the readiness of educators and technology resources, and adaptive learning implementation design play a crucial role in improving the quality of podcast utilization. Continuous curriculum evaluation is also necessary to ensure podcasts align with learning objectives and student characteristics. These findings confirm that integrating podcasts into curriculum management can enhance a more flexible, interactive learning experience, and adapt to the digital era.